BENEFITS OF BINDING MATERIALS ON THE TASTE OF TENGGIRI FISH NUGGET (SCOMBEROMORUS SP) - Kaliky, Nurainy (International Journal of Multidisciplinary Research and Literature, 2022)
Nugget is a processed product from fish that has good nutritional value and is in great demand by various circles of society. Nuggets can be made from all types of fish, both marine and freshwater fish. Fish As a raw material for making fish nuggets, because it has a fairly high amount of protein in fish meat. Protein is needed by the human body to help the growth process, especially in children. Nuggets are also a favorite food that is very popular with children. To produce nuggets with a good texture, the fish used as raw material is white-fleshed fish. One of the fish used in making these nuggets is ternggiri fish (Scomberomorus sp). Nuggets are food made from fish meat that has been mashed and seasoned then steamed and fried. This study aims to increase the taste of mackerel fish nuggets (Scomberomorus sp) various additions of binders and to increase public knowledge in processing fish without reducing its nutritional value. A2 = 80 gr ; Trea tment B ( Concentration of Wheat flour): B1= 60gr, B2=80 Gr; Treatment C (steaming temperature); 86º- 95º C for 40 minutes with 2 repetitions. The results obtained for the organoleptic parameters of color, taste,Texture and smell gave good values ​​and these three parameters did not show a significant effect